A retrospective comparative outcome analysis following systemic therapy in Mycosis fungoides and Sezary syndrome. Issue 12 (December 2016) - Hanel, Walter; Briski, Robert; Ross, Charles W.; Anderson, Thomas F.; Kaminski, Mark S.; Hristov, Alexandra C.; Wilcox, Ryan A
Abstract : Cutaneous T‐cell lymphomas (CTCL), with few exceptions, remain incurable and treatment is largely palliative. We performed a retrospective analysis of systemic treatment outcomes of patients diagnosed with MF/SS. We identified 223 patients with MF/SS evaluated at a single institution from 1997 to 2013. Disease stage at diagnosis, time of treatment, and treatments received were retrospectively analyzed using our CTCL database. The primary endpoint was time to next treatment (TTNT). Treatment outcomes were analyzed using Kaplan–Meier method and comparisons among groups were made using log‐rank analysis. A superior TTNT was associated with retinoid or interferon therapies when compared with HDAC inhibitors or systemic chemotherapy. Retinoids and interferon were associated with superior TTNT in both limited‐stage and advanced stage disease. Extracorporeal photophoresis (ECP) had a superior TTNT in Sezary Syndrome. HDAC inhibitors and chemotherapy were associated with inferior TTNT in both limited stage disease and advanced stage disease. With the exception of interferon, retinoids, or ECP, durable responses are rarely achieved with systemic therapies in MF/SS patients, particularly those with advanced‐stage disease. Therefore, clinical trial participation with novel agents should be encouraged. Am. J. Hematol. 91:E491–E495, 2016. © 2016 Wiley Periodicals, Inc.